INNOVATIVE APPROACHES TO THE DEVELOPMENT OF ENGINEERING AND TECHNICAL EDUCATION (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article analyzes the strategic directions of modern engineering and technical education. It discusses the reforms being implemented in the higher education system, the integration of education with production, and the importance of innovative approaches in training qualified personnel. The author justifies the need to modernize engineering education in the context of technological innovations in industry, changes in the labor market, and global trends. It also considers the problems and solutions of effectively organizing independent work in distance education and improving the quality of education in harmony with science.